Trends in the development of hr outsourcing - Tovazhnyanskyy, P. V.; Pererva, P. G. (Луцький національний технічний університет, 2022)
It is proposed to define complex outsourcing of personnel as the transfer of all personnel management processes to another company, in contrast to service and auxiliary services, which are of a one-time, occasional nature, in this case, ordinary functions for professional support and uninterrupted operation of the system are transferred to the outsourcing on the basis of a long-term contract (not less than 1 year).
Тенденції розвитку кадрового аутсорсингу
Keywords: personnel outsourcing; management; demand; supply; efficiency; enterprises